Wet-spun Ag/PEDOT: PSS composite fibers for high-sensitive SERS sensing and high electrical conducting - Fan Wu; Haoyu Shi; Yulong Gao; Lin Cheng; Tongkai Gu; Tong Liu; Ziyun Chen; Wei Fan (Scientific Reports)
Abstract Nanometal-based composite fibers have been widely explored in flexible sensors due to their outstanding optical and electrical properties. However, the weak binding force between metallic nanomaterial and fiber greatly limits the real application. In this work, nano silver (Ag) are strongly bonded with poly(3,4-ethylenedioxythiophene)-poly (styrene sulfonate) (PEDOT: PSS) fiber by the wet-spun process. Ag-S chemical bonds are formed by the interaction of Ag and PEDOT. The Ag/PEDOT: PSS composite fiber shows excellent surface-enhanced Raman scattering (SERS) sensitivity on Rhodamine 6G (R6G) molecules. The detection limit can reach 10–11 M and Raman enhancement factor (EF) is of 1.3 × 107. The high-sensitive SERS activity of Ag/PEDOT: PSS composite fiber mainly results from PEDOT: PSS, and the enhancement factor is 3 orders of magnitude better than that of other PEDOT: PSS based SERS substrates. Moreover, the composite fiber has metal-level conductivity of 1019 S/cm. This is 5 times higher than the conductivity of PEDOT: PSS fiber and a two-fold improvement over the reported values for nanometal/PEDOT: PSS based fabrics. The composite fiber has electric stability under bending test with bending speeds of 2 Hz indicating the composite fiber has good structural stability. In addition, the temperature of the composite fiber with 7 cm length can reach 76.5 °C at a voltage of 18 V. Additionally, the composite fiber shows anti-bacterial property and melting drop resistance, which pave the way for the integration of fiber-based optical and electrical sensors in the future multifunctional flexible devices.